Workload changes during the COVID-19 pandemic and effects on the flow of cancer patients in the Maxillofacial Surgery Department - Ana Kvolik Pavić; Vedran Zubčić; Slavica Kvolik (Medicinski glasnik, 2020)
Aim: A SARS Coronavirus 2 (COVID-19) pandemic drastically changed the way the health system works. In Croatia, lockdown measures to curb virus spread lasted from March to May 2020, and all non-essential medical procedures and patients’ visits have been cancelled. The study aimed to compare patients’ flow and interventions in the surgical department before, during and after the lockdown period. Methods: This cross-sectional study analysed the workload at the Maxillofacial and Oral Surgery Department (Department), Osijek University Hospital, during the COVID-19 pandemic (March-May 2020) and four subsequent months. The same period of 2019 was compared as a control. The data were subtracted from hospitals’ electronic database. Results: During COVID-19 lockdown from March to May 2020 the number of hospitalizations (306 vs. 138), surgical procedures (306 vs. 157), and scheduled outpatient visits (2009 vs. 804), dropped significantly as compared to 2019. The number of skin tumour removals was halved (from 155 in 2019 to 58 in 2019) (p<0.001), and the number of emergency patients was unchanged in the 3-month period. A significant decrease in outpatient visits and hospital admissions continued after the lockdown (p<0.001). Conclusion: A decrease in the number of outpatient visits, hospitalizations, and tumour removals may result in larger proportions of patients with advanced cancers in the future. The second wave of COVID-19 pandemic is ongoing, and special effort must be paid to reduce the number of cancer patients receiving suboptimal treatment.
Keywords: head and neck neoplasms; time-to-treatment; workflow